Existence and Uniqueness for a Class of SPDEs Driven by Lévy Noise in Hilbert Spaces - Majid Zamani; S. Mansour Vaezpour; Erfan Salavati (Sahand Communications in Mathematical Analysis, 2021)
The present paper seeks to prove the existence and uniqueness of solutions to stochastic evolution equations in Hilbert spaces driven by both Poisson random measure and Wiener process with non-Lipschitz drift term. The proof is provided by the theory of measure of noncompactness and condensing operators. Moreover, we give some examples to illustrate the application of our main theorem.